Linearização de sistemas de controle - Fernando Cordeiro de Queiroz (2016)
In this work we study some classical results of the control theory. We will demonstrate the Kalman Condition for controlability of linear systems, the Orbit Theorem and Rashevsky-Chow and Krener theorems. We will also discuss the classification of linear controllable systems, through of the Brunovský normal form. Finally, we present the main result in this dissertation: to establish conditions in order to affine control system be equivalent to a controllable linear system